PENDAMPINGAN PROGRAM JARING PENGAMAN SOSIAL: STUDI DAMPAK SOSIO EKONOMI COVID-19 BERDASARKAN MAQASHID SYARIAH DI KABUPATEN NGANJUK - Tika Widiastuti; Puji Sucia Sukmaningrum; Muryani Muryani; Aufar Fadlul Hady (Universitas Airlangga, 2021)
AbstractThis community service activity, which is packaged in the form of mentoring, aims to assist stakeholders in Sugihwaras village, Prambon sub-district, Nganjuk Regency to synergize with each other in handling the impact of the COVID-19 pandemic. In addition, this assistance aims to provide a model of distribution of assistance that meets basic human needs following the Dharurriyatul Khams concept in Maqashid Syariah. These basic needs include the protection of religion, soul, mind, lineage, and property. Community service has increased public awareness regarding the importance of synergy between stakeholders during the pandemic and understanding the types of assistance that must be prioritized referring to the maqashid sharia concept. The impact of this assistance is the strength of the village economic structure because the community helps each other strengthen the collaborative economy.Keywords: Assistance, Sinergyz, Maqashid ShariahAbstrakKegiatan pengabdian masyarakat yang dikemas dalam bentuk pendampingan ini bertujuan untuk memberikan pendampingan kepada stakeholder di desa Sugihwaras, kecamatan Prambon, Kabupaten Nganjuk untuk saling bersinergi dalam penanganan dampak pandemi COVID-19. Selain itu, pendampingan ini bertujuan untuk memberikan sebuah model penyaluran bantuan yang memenuhi kebutuhan dasar manusia sesuai dengan konsep Dharurriyatul Khams dalam Maqashid Syariah. Kebutuhan dasar tersebut meliputi perlindungan agama, jiwa, akal, keturunan, dan harta. Pengabdian masyarakat berhasil meningkatkan kesadaran masyarakat terkait pentingnya sinergi antar pemangku kepentingan stakeholder dalam masa pandemi serta pemahaman mengenai jenis bantuan yang harus diprioritaskan mengacu kepada konsep maqashid syariah. Dampak dari pendampingan ini adalah kuatnya struktur ekonomi desa karena masyarakat saling membantu dalam penguatan ekonomi bersama.Kata Kunci: Pendampingan, Sinergi, Maqashid Syariah